Entrepreneurial Orientation and Innovation on Competitive Advantage - Maulana Ibrahim, Afif; Ali, Hapzi (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Competitive advantage is the main goal for companies in a dynamic and competitive business environment. Two important factors that influence competitive advantage are entrepreneurial orientation and innovation. Entrepreneurial orientation encourages companies to always look for new opportunities in the market, while innovation allows companies to continuously adapt and offer unique products or services. This article aims to examine the influence of entrepreneurial orientation and innovation on competitive advantage based on existing literature. The results of this study are (1) Entrepreneurial orientation has a significant influence on Competitive Advantage. (2) Innovation has a significant influence on Competitive Advantage. (3) Entrepreneurial orientation and Innovation have a simultaneous influence on competitive advantage.